PENGARUH MOTIVASI KERJA, DISIPLIN DAN ETOS KERJA TERHADAP PERILAKU KEPEMIMPINAN PADA KANTOR PELAYANAN PEMBENDAHARAAN NEGARA (KPPN) KOTA PALEMBANG - Puput Anduana Putri; Maya Panorama; Rizky Ramadhani Putri; Epi Royani Misrawati (JPSDa: Jurnal Perbankan Syariah Darussalam, 2022)
Abstract Motivation is an encouragement to someone in order to achieve the desired goal. With the motivation to improve employee performance and work discipline in the company. The purpose of this study was to determine whether work motivation has a direct effect on employee performance and to determine whether work discipline mediates the effect of work motivation on employee performance at the Palembang City State Treasury Service Office (KPPN). The research variables used were work motivation, discipline and work ethic as independent variables and employee performance as the dependent variable. Data analysis used multiple linear regression. The results of the study are in line with the theoretical study used in this study, namely for the work motivation variable in accordance with Herzberg's theory that motivation can form a person who can improve performance in achieving organizational goals, for the leadership style variable in line with the Target Path theory developed by Robert House where Leadership can help employees to improve their performance. As for the work discipline variable, it is in line with Hasibuan's opinion where work discipline will affect the performance of the employee concerned. Thus, the results of the study show that the variables of work motivation, work discipline and work ethic have a significant influence on leadership at KPPN Palembang City. Keywords: Motivation, Work Discipline, Work Ethic, and leadership behavior